2010
DOI: 10.3109/15563650.2010.517208
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis associated with usage of herbal slimming products adulterated with sibutramine: a case series

Abstract: Slimming products claimed "herbal" in origin could often be adulterated with sibutramine and other Western medications. We observed an association between the use of these products and psychotic features. Further studies are warranted to study whether these adverse events are an uncommon adverse drug reaction of sibutramine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…It has already spread to another life-style drug (sibutramine) and might as well spread to essential drugs [100][101][102]. Proactive regulation of all possible analogues of registered ED drug substances may be useful.…”
Section: Discussionmentioning
confidence: 98%
“…It has already spread to another life-style drug (sibutramine) and might as well spread to essential drugs [100][101][102]. Proactive regulation of all possible analogues of registered ED drug substances may be useful.…”
Section: Discussionmentioning
confidence: 98%
“…[165] Among the 62 samples that tested positive, 25 contained sibutramine, desmethylsibutramine, and didesmethylsibutramine as well as other weight loss compounds. [166] Sibutramine was detected and quantified by GC-MS in five slimming food samples collected in China. [165] A series of 17 cases of documented poisonings in Germany from 2005 to 2008 revealed that sibutramine-containing products were involved in all of the cases.…”
Section: Drug Testing and Analysismentioning
confidence: 99%
“…Bu olgularda halsizlik, bulantı-kusma, ağız kuruluğu, konstipasyon, uykusuzluk, ajitasyon, baş ağrısı, halüsinasyon, taşikardi, hipertansiyon, dispne, ateş bildirilmiştir. [14][15][16] Olgumuzun kullandığı ürünün içeriği tarafımızdan tetkik edilememiş olmakla beraber taşikardi ve hipertansiyon gözlenmesi ürünün içinde sibutramin olabileceğini düşündürmektedir.…”
Section: Olgu Sunumuunclassified